Development of a Canva-Based English Picture Dictionary Application for Seventh-Grade Students - Denista Riska Cahyani Mendrofa; Elwin Piarawan Zebua; Kristof Martin Efori Telaumbanua; Riswan Zega (Universitas Pendidikan Mandalika, 2026)
This study aims to develop a Canva-based English picture dictionary application designed to enhance seventh-grade students’ reading interest and vocabulary mastery. The study employed a Research and Development (R&D) method combined with a Classroom Action Research (CAR) approach conducted in two cycles. The participants were seventh-grade students at SMP Swasta Kristen Tomosa 1. Research instruments included interviews, classroom observations, questionnaires, and vocabulary tests. Data were analyzed using descriptive quantitative and qualitative techniques. The results indicate that the use of the picture dictionary significantly increased students’ interest in learning and vocabulary mastery, as evidenced by improvements in questionnaire responses and test scores across the two cycles. The mean vocabulary score increased from 49.61 in the pre-test to 86.53 in the post-test. Consistent questionnaire scores across Cycle 1 and Cycle 2 (4.61) indicate the reliability and stability of the learning media. Students’ understanding of new vocabulary reached a mean score of 4.78 (95.6%), while their understanding of word meanings increased to 4.71 (94.2%). Students’ interest in learning English also improved, with a mean score of 4.64 (92.8%). Overall, the findings demonstrate that the Canva-based picture dictionary is an effective learning medium for enhancing students’ interest and vocabulary mastery in English language learning by providing engaging visual support that promotes active and motivated learning.